2007
DOI: 10.1021/jf063711a
|View full text |Cite
|
Sign up to set email alerts
|

Echinacea Species and Alkamides Inhibit Prostaglandin E2 Production in RAW264.7 Mouse Macrophage Cells

Abstract: Inhibition of prostaglandin E 2 (PGE 2 ) production in lipopolysaccharide-stimulated RAW264.7 mouse macrophage cells was assessed with an enzyme immunoassay following treatments with Echinacea extracts or synthesized alkamides. Results indicated that ethanol extracts diluted in media to a concentration of 15 μg/ mL from E. angustifolia, E. pallida, E. simulata, and E. sanguinea significantly inhibited PGE 2 production. In further studies, PGE 2 production was significantly reduced by all synthesized alkamides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 33 publications
3
60
3
Order By: Relevance
“…It is noteworthy that the synergistic action of NAAs has been demonstrated in numerous studies involving different antiinflammatory pathways (PGE2/5-HPETE/cytokine levels, NF-kB activity, CB2 activation) (Chicca et al, 2009;Lalone et al, 2007;Matthias et al, 2008Matthias et al, , 2007Mullerjakic et al, 1994;Woelkart et al, 2006). This again indicates the importance of the knowledge of phytochemical components present in an investigated and/or used extract.…”
Section: Anti-inflammatory and Immunomodulatory Effectsmentioning
confidence: 89%
See 1 more Smart Citation
“…It is noteworthy that the synergistic action of NAAs has been demonstrated in numerous studies involving different antiinflammatory pathways (PGE2/5-HPETE/cytokine levels, NF-kB activity, CB2 activation) (Chicca et al, 2009;Lalone et al, 2007;Matthias et al, 2008Matthias et al, , 2007Mullerjakic et al, 1994;Woelkart et al, 2006). This again indicates the importance of the knowledge of phytochemical components present in an investigated and/or used extract.…”
Section: Anti-inflammatory and Immunomodulatory Effectsmentioning
confidence: 89%
“…At higher concentrations i.e. from 12.5 mg/mL, also NAAs containing double bonds in their acid chain have an inhibitory effect on the COX proinflammatory PGE2 product (23% up to 90% inhibition) (Cech et al, 2010;Hinz et al, 2007;Lalone et al, 2007;Mullerjakic et al, 1994). In the fatty acid part of the NAA, the 2E configuration shows a higher inhibitory effect than the 2Z configuration, (e.g.…”
Section: Anti-inflammatory and Immunomodulatory Effectsmentioning
confidence: 99%
“…Echinacea purpurea Moench (E. purpurea) is an indigenous medicine of the native American Indians and Europeans with multiple biological activities, such as anti-inflammation, anti-oxidation, anti-bacteria, antiproliferative, antihypertensive and immunomodulation effects for hundreds of years (Aarland et al, 2017;Chiou et al, 2017;LaLone et al, 2007). This medicinal plant was also used as food supplements in infectious diseases in children, old people and animals in North America and Europe (Ayrle et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A possible action of the treatments is that these chemical mediators are altered. In this respect, affinin is an alkamide, and it has been found that alkamides can inhibit the production of PGEs (Prostaglandins) (LaLone et al, 2007). Given that the abdominal contraction relates to the sensitization of prostaglandin-nociceptive receptors and of sympathetic nervous system mediators, it is likely that affinin and the ethanol extract inhibit either their synthesis or the contact with their receptors, thereby producing the analgesic effect.…”
Section: Discussionmentioning
confidence: 99%